2015
DOI: 10.3390/rs70505697
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Comparison of TMPA Satellite Precipitation Products in Varying Climatic and Topographic Regimes in Morocco

Abstract: TRMM Multi-satellite Precipitation Analysis (TMPA) satellite precipitation products have been utilized to quantify, forecast, or understand precipitation patterns, climate change, hydrologic models, and drought in numerous scientific investigations. The TMPA products recently went through a series of algorithm developments to enhance the accuracy and reliability of high-quality precipitation measurements, particularly in low rainfall environments and complex terrain. In this study, we evaluated four TMPA produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 76 publications
4
67
1
1
Order By: Relevance
“…Results indicated that the accuracy was higher on basin scale compared with pixel scale and overall performance of monthly 3B42V7 estimates was better than that of monthly 3B42V6 and 3B42RT data. These findings are consistent with previous literature [14,18].…”
Section: Evaluation Of Tmpa Products At Different Spatial and Temporasupporting
confidence: 83%
See 1 more Smart Citation
“…Results indicated that the accuracy was higher on basin scale compared with pixel scale and overall performance of monthly 3B42V7 estimates was better than that of monthly 3B42V6 and 3B42RT data. These findings are consistent with previous literature [14,18].…”
Section: Evaluation Of Tmpa Products At Different Spatial and Temporasupporting
confidence: 83%
“…A large number of studies have evaluated the performance of 3V42V6 in many parts of world [11][12][13][14][15]. Although some studies have also documented the performance of 3B42V7 in different regions of the world [14][15][16][17][18], limited studies have reported on its performance relative to its predecessor (3B42V6) and near real time product (3B42RT) in complex terrain regions having cryospheric environment. Thus, a river basin situated in the high mountains of Hindukush-Karakoram-Himalayan (HKH) region [15,19] has been chosen for undertaking a comprehensive and comparative assessment of TMPA products with a wide variety of statistical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies [18,[45][46][47][48][49] have used gauge measurements to validate the accuracy of TMPA products. In this study, the error characteristics of IMERG monthly precipitation products over Mainland China were evaluated using gauge measurements at multiple spatiotemporal scales.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have linked rainfall deficits, soil thermal stress and vegetation growth and mortality to drought [2,3,[5][6][7]9,11,12,15,20,25,[27][28][29][30][31][32]36,[50][51][52], highlighting the need for operational drought monitoring systems that can show drought intensity, location and extent [16]. In response, this study devised an operational procedure and algorithm, a run-off model, from TMPA rainfall and MODIS evapotranspiration products for spatiotemporal drought assessment (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%